1243. Comparative Analysis of Antimicrobial-related Adverse Events in the Outpatient Treatment of Staphylococcal Infections. (26th November 2018) - Smith, Bradley; Rivera, Christina; Dierkhising, Ross; Estes, Lynn; O'Horo, John; Tande, Aaron; Zeuli, John; Virk, Abinash
Abstract: Background: Limited data exist to evaluate safety-related outcomes in Outpatient Parenteral Antimicrobial Therapy (OPAT) patients treated with antimicrobial agents for Gram-positive infections. Methods: This retrospective, single-center study enrolled Mayo Clinic OPAT patients between 2013 and 2017. The primary objective of the study compared rates of therapy modification due to drug-related toxicity for staphylococcal infections treated with ceftriaxone, cefazolin, nafcillin, oxacillin, vancomycin, daptomycin, ceftaroline, linezolid, or ertapenem. Secondary objectives included determination of the frequency and type of adverse drug events (ADEs) attributed to OPAT and rate of readmission due to ADEs attributed to OPAT. Results: One hundred seventy-two patients were identified (cefazolin n = 54, ceftriaxone n = 49, vancomycin n = 30, daptomycin n = 16, nafcillin n = 9, ertapenem n = 6, ceftaroline n = 4, oxacillin n = 3, linezolid n = 1). The overall treatment completion rates were high (153/172, 89.0%). Patients completed an average of 35.3 days (7 to 95) of therapy with their original antibiotic. Fourteen patients required change to a different antibiotic due to antimicrobial toxicity (ceftriaxone=5; vancomycin=2; cefazolin = 2; daptomycin = 2; ceftaroline = 1; nafcillin = 1; oxacillin = 1) and five patients experienced treatment failure required an additional agent (ceftriaxone = 2; nafcillin = 2; linezolid = 1). Adverse drug events (ADEs) were the most common reason for antimicrobial adjustment (14/19, 73.7%). The most common ADEs were hypokalemia (28/172, 16.3%) and diarrhea (25/172, 14.5%). There were only two cases of Clostridium difficile. Thirty-day readmissions due to antimicrobial therapy were low with 11 patients. Conclusion: OPAT with Gram-positive agents used for staphylococcal infections is effective, but antimicrobial modifications still occur. Clinicians should be aware of the risk of ADEs and readmissions in OPAT patients. A multidisciplinary approach may enhance management of ADEs and possibly preventing readmissions Disclosures: All authors: No reported disclosures.